Konsumsi Media Sosial Tik Tok pada Mahasiswa Universitas Sriwijaya Kampus Indralaya - Shafirah Pertiwi (Master Program in Sociology, Faculty of Social and Political Science, Universitas Sriwijay, 2021)
This research is entitled